If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-66=-8z+2z
We move all terms to the left:
-66-(-8z+2z)=0
We add all the numbers together, and all the variables
-(-6z)-66=0
We get rid of parentheses
6z-66=0
We move all terms containing z to the left, all other terms to the right
6z=66
z=66/6
z=11
| 3p-5=2(4p-20) | | 6=-2(7-e) | | 44=-2w-2w | | 5x•=x | | -4(d-12)=40 | | 45+2e=12-e | | 52=4+3(2x+10) | | 8a+20=4(2a+5) | | 2=p+11/4 | | 4x-2x+2x-3x=9+6 | | 2g+18=3(2g-6) | | -17.32=-1.6+4.4r+3.2 | | 400+x=6800 | | -15=-9d-6d | | 8y-13y-2=15 | | 5(2x+3)-5=40 | | 4/5=m/4 | | 5(p+3)+1=-29 | | 24=10y+2y | | -4(3v+7)-3v=-133 | | 3(2x-3)-2(1-3x)=61 | | 7=1+3w | | 2x+10+4x-2=140 | | -12x-7=18 | | 3^2b+6+1*2b=15+2b | | 9w-23=13+3w | | 30=9(10-2x) | | -7(y-4)=-21 | | 1-8(x-6)=105 | | 3c=5=23 | | 5x2−19x+6=0 | | 2/k-2=5 |